TAXONOMIC AND NOMENCLATURAL NOTES ON PHILIPPINE FERNS II: THREE NEW NAMES IN ASPLENIUM - SALGADO, E. (Edinburgh Journal of Botany, 2005)
The new names Asplenium luzonicum and A. perplexum are published to replace the homonyms A. cristatum Brack. and A. riparium Brack.; their nomenclatural history is reviewed and data are provided to support their retention as separate species. The legitimate name A. baileyanum should be used instead of the homonym A. gracile Fée.
Keywords: Asplenium baileyanum; A. cristatum; A. gracile; A. luzonicum; A. perplexum; A. riparium; Malesia